Religiositas, olahraga dan etika belaskasih (hesed): Religiosity, sports and the ethics of mercy (hesed) - Victor Christianto; Isak Suria; Talizaro Tafonao (Jurnal Teologi Amreta (ISSN: 2599-3100))
In this reflective article, the writers study Religiosity, sports and the ethics of mercy (hesed). This study departs from the author's observation of one of John Ortberg’s books. Ortberg explained in his work, among others that in the area of spirituality we often play like we want to score in basketball or baseball, with the hope of scoring as much as possible, whether quantitatively or qualitatively. Based on this thought, the writers observe the text of Philippians 2: 6-8, that Jesus is the only servant who can be emulated in all things by giving up the totality of His life for the sake of humanity. The uniqueness of Jesus as a servant of God has been reflected in the story of His life, namely He was born in a cage of animals and served indefinitely. And at the end of His life, He was willing to die in the most despicable state of being crucified. The story of Jesus is the story of God descending to earth who took on human appearance. The method used is a qualitative research method, and the authors examine the Philippian text to analyze the Bible's view of Religiosity, sport and the ethics of mercy (hesed). The reflective study process carried out by these authors is to use a variety of reliable library and electronic sources to support the authors's analysis. The results of this study, which were intended from the beginning as reflective narratives rather than theoretical analysis, are to believe that Jesus came down to earth as a manifestation of God's love from Heaven, and that should be an example for us all as His disciples. ====== Dalam tulisan berciri reflektif ini, penulis melakukan kajian terhadap Religiositas, olahraga dan etika belaskasih (hesed). Kajian ini berangkat dari pengamatan penulis terhadap sebuah buku John Ortberg. Ortberg menjelaskan dalam karyanya tersebut antara lain bahwa dalam area spiritualitas seringkali kita bermain seperti ingin mencetak skor dalam basket atau baseball, dengan harapan mencetak skor sebanyak-banyaknya, apakah secara kuantitatif atau secara kualitatif. Berdasarkan pemikiran tersebut, maka penulis mengamati teks Filipi 2:6-8, bahwa Yesus adalah satu-satunya hamba yang dapat diteladani dalam segala hal dengan menyerahkan totalitas hidup-Nya demi umat manusia. Keunikan Yesus sebagai hamba Tuhan telah tercermin dalam kisah hidup-Nya, yakni Dia lahir di kandang hewan dan melayani tanpa batas waktu. Dan pada akhir hidupNya, Dia rela mati dalam keadaan yang paling hina yakni disalibkan. Kisah Yesus adalah kisah Allah yang turun ke bumi yang mengambil rupa manusia. Metode yang digunakan adalah metode penelitian kualitatif, penulis mengkaji teks Filipi untuk menganalisis pandangan Alkitab mengenai Religiositas, olahraga dan etika belaskasih (hesed). Proses kajian reflektif yang dilakukan oleh penulis adalah menggunakan berbagai sumber pustaka maupun elektronik yang terpercaya untuk mendukung analisis penulis. Hasil penelitian ini, yang memang dari awal diniatkan sebagai narasi reflektif bukan teoritis analisis, hendak mengimani bahwa Yesus turun ke bumi sebagai perwujudan dari kasih Allah dari sorga, dan hal tersebut semestinya menjadi teladan bagi kita semua sebagai murid-murid-Nya.